Modern approach to the clinical management of non-alcoholic fatty liver disease - Del Ben, Maria (Baishideng Publishing Group Inc, 2014)
Non-alcoholic fatty liver disease (NAFLD) is the most common and emerging form of chronic liver disease worldwide. It includes a wide spectrum of liver diseases ranging from simple fatty liver to steatohepatitis, which may progress to cirrhosis, liver cancer, and liver mortality. Common metabolic diseases, which are well established cardiovascular risk factors, have been associated to NAFLD and cardiovascular disease is the single most important cause of morbidity and mortality in this patient population. The pathogenesis of NAFLD appears multifactorial and many mechanisms have been proposed as possible causes of fatty liver infiltration. Management of fatty liver has become a major challenge to healthcare systems as the consequence of the increasing rates of obesity worldwide. First-line management focuses on lifestyle modifications. Moderate weight reduction either by dietary restriction or by increased habitual physical activity is safe and highly recommended. Several therapeutic interventions have been proposed. These include insulin sensitizer agents, lipid lowering drugs, antioxidants such as vitamin E and supplementation of vitamin D(3). However, therapeutic strategies have been largely empirical so far, and experimental trials have mostly been carried out in uncontrolled settings with small sample sizes. Metabolic conditions such as diabetes mellitus, obesity, hypertension and hyperlipidemia, should be strongly considered and a multidisciplinary approach should be personalized for individual patients. Treatment of co-morbidities should be regarded as of paramount importance in the management of these patients. The purpose of this review is to examine different approaches for the clinical management of non-alcoholic fatty liver disease.